Left behind?: male clients of female sex workers in Zambia. Issue 12 (1st December 2020) - Carrasco, Maria A.; Rosen, Joseph G.; Phelps, Ryan
ABSTRACT: Male clients of female sex workers (CFSWs) are a key-affected group within the HIV epidemic. However, few studies have quantified HIV/STI burdens among CFSWs. This study used nationally representative data from the 2013–14 Zambia Demographic and Health Survey to estimate proxies for HIV and STI prevalence among sexually active men aged 15–59 paying for sex recently (past 12 months) [5%, n = 679] or in their lifetime [15%, n = 1, 887]. Chi-square tests were calculated to assess differences in prevalence estimates between CFSWs and non-clients. Multivariable logistic regression models were generated to identify sociodemographic factors associated with prevention characteristics. CFSWs had higher odds of reporting HIV infection (recent: aOR 1.413, p  < 0.05; lifetime: aOR 1.604, p  < 0.001) and past-year STI symptomology (recent: aOR 3.342, p  < 0.001; lifetime: aOR 2.266, p  < 0.001) than non-clients, irrespective of transactional sex recency. Compared to non-clients, CFSWs were more likely to be <25yo (42% vs. 29%, p  < 0.001), have a cohabitating partner (43% vs. 35%, p  < 0.001), use condoms at last sex (31% vs. 27%, p  < 0.001), and never test for HIV (36% vs. 29%, p  < 0.001). When comparing CFSWs to non-clients, marital status was an effect modifier of HIV testing, medical circumcision, and condom use at last sex. Findings suggest high HIV/STI burdens and highlight the urgent need for differentiated HIV prevention programming for CFSWs in Zambia including the provision of PrEP.